Implementasi Manajemen keuangan Sederhana bagi Siswa Teknik Mesin untuk Menumbuhkan Sikap Menghargai Rupiah Tanpa Judi Online Di SMK Persada Bhakti - Tutik Yuliani; Dika Karlinda Sari; Dwi Susilowati; Fransiskus Antonius Pabaru; Nur Raihaine Fetry (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The purpose of this Community Service activity is to provide students with an understanding of how to respect the rupiah without resorting to online gambling through the socialization activity "Respecting the Rupiah Without Online Gambling Through Education and Solutions" at SMK Persada Bhakti. The method used in this activity was a socialization combined with discussion and questions and answers between participants and speakers. The results of this community service activity were able to increase students' knowledge regarding the importance of capital markets respecting the rupiah without online gambling, this was demonstrated by all students participating in questions and answers related to the material presented. Education has proven to be one of the most effective interventions to respect the rupiah and prevent dependence on online gambling from an early age. Continuity of the program and support from all parties are needed for a broader and more sustainable impact.